PROVISION COMBINATION OF CERVICAL TRACTION AND NEURAL MOBILIZATION MODALITY IN PHYSIOTHERAPY MANAGEMENT IN CERVICAL RADICULOPATHY: A CASE REPORT - Kurniansari, Anggun Agiel; Pristianto, Arif; Rochmaningtyas, Putri (Universitas Muhammadiyah Surakarta, 2021)
Introduction: Cervical radiculopathy (CR) is a condition described as neck pain radiating to one or both sides of the upper limb, allowing sensory, reflex and even motor disturbances to occur. The incidence of CR was recorded as 1.07-1.75 per 1000 males and 0.68-5.8 per 1000 females. Most of the improvement was obtained through non-surgical measures, that physiotherapy management will be described in the form of a combination of cervical traction (CT) and neural mobilization (NM) modalities. Case Presentation: A 52-year-old female patient complained of neck pain up to her left arm, appeared forward head posture, was diagnosed with cervical radiculopathy due to narrowing of the intervertebral disc from C5-7 (SMRI results). Management and Outcome: After 6 treatments, pain reduction was obtained from T0: 4/10 to T5: 2/10 numeric rating scale (NRS), the results of the goniometer measurement of the joint range of motion (ROM) neck flexion T0:42o to T5:45o and decreased disability rate from 35% (T0) to 42% (T5) neck disability index (NDI) score. Discussion: The use of CT provides a short-term analgesic effect, increasing the intervertebral foramen space that the pressure between the discs decreases. While the NM technique will increase the ability of nerve gliding and decrease nerve mechanosensitivity. Conclusion: The combination of CT and NM modalities can reduce pain, increase ROM and decrease disability in CR patients.